2001
DOI: 10.1902/jop.2001.72.10.1324
|View full text |Cite
|
Sign up to set email alerts
|

The Fcγ Receptor Genotype as a Severity Factor for Chronic Periodontitis in Japanese Patients

Abstract: Our results document the Fc gamma RIIIa-158V allele and possibly Fc gamma RIIIb-NA2 to be associated with severity of CP in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 40 publications
10
69
2
3
Order By: Relevance
“…FcgRIIIAÀ158V and FcgRIIIB-NA2 were recently shown as a severity factor for CP. 28 In this study, we found no linkage disequilibrium between FcgRIIB-nt 646À184A/G and other FcgRIIA, IIIA and IIIB polymorphisms. These results suggested the FcgRIIB-nt 646À184A/G genotype to be a susceptibility factor for CP.…”
Section: Discussionmentioning
confidence: 40%
“…FcgRIIIAÀ158V and FcgRIIIB-NA2 were recently shown as a severity factor for CP. 28 In this study, we found no linkage disequilibrium between FcgRIIB-nt 646À184A/G and other FcgRIIA, IIIA and IIIB polymorphisms. These results suggested the FcgRIIB-nt 646À184A/G genotype to be a susceptibility factor for CP.…”
Section: Discussionmentioning
confidence: 40%
“…NA1 is found to a greater extent in Japanese patients who are resistant to chronic periodontitis (OR 1.87, 95% CI 1.07-3.28). Kobayashi et al (2001) reported that 2 Fc␥RIII alleles may be associated with severity of chronic periodontitis in a Japanese population. Meisel et al (2001) analyzed the association between Fc␥RIIIa (high-affinity receptor) and Fc␥RIIIb (low-affinity receptor) and chronic periodontitis (CP).…”
Section: (9) Fc-gamma Receptormentioning
confidence: 99%
“…27 In contrast, another Japanese researchers reported that the FcγRIIIa-158V allele was over-represented in patients with severe periodontitis versus subjects with moderate disease. 28 In this study, a significant association was observed between the FcγRIIIa-158V/F polymorphism and AgP patients. Moreover, the FcγRIIIa-158F allele was more frequently detected in AgP over healthy controls.…”
Section: Distribution Of Fcγriii Genotypes and Allelesmentioning
confidence: 50%